PENGARUH KEPEMIMPINAN, BUDAYA KERJA DAN TUNJANGAN KINERJA TERHADAP KINERJA PEGAWAI - Sri Sulistyowati; Pompong B. Setiadi; Sri Rahayu (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to analyze the influence of leadership, work culture and performance benefits on employee performance. The research was aimed at employees of the logistics bureau of the East Java regional police. The research respondents totaled 54 people with the type of research sample selection, namely purposive sampling or determining the sample based on the research objectives. The research method applied was a survey using a questionnaire with reference to the Likert scale and the type of research was exploratory research. The data analysis method applies multiple linear regression, hypothesis testing and the coefficient of determination. The data processing stage uses the IBM Version 25 Statistical Application Solutions (SPSS). The results of the study show that the variables of work culture and employee performance have a partial effect, while the leadership variable has no partial effect on employee performance.